Global Molecular Analyses of Methane Metabolism in Methanotrophic Alphaproteobacterium, Methylosinus trichosporium OB3b. Part I: Transcriptomic Study - Matsen, Janet B.; Yang, Song; Stein, Lisa Y.; Beck, David A.; Kalyuzhanaya, Marina G. (Frontiers in Microbiology, 2013)
Methane-utilizing bacteria (methanotrophs) are important in both environmental and biotechnological applications, due to their ability to convert methane to multicarbon compounds. However, systems-level studies of methane metabolism have not been carried out in methanotrophs. In this work we have integrated genomic and transcriptomic information to provide an overview of central metabolic pathways for methane utilization in Methylosinus trichosporium OB3b, a model alphaproteobacterial methanotroph. Particulate methane monooxygenase, PQQ-dependent methanol dehydrogenase, the H4MPT-pathway and NAD-dependent formate dehydrogenase are involved in methane oxidation to CO2. All genes essential for operation of the serine cycle, the ethylmalonyl-CoA (EMC) pathway, and the citric acid (TCA) cycle were expressed. PEP-pyruvate-oxaloacetate interconversions may have a function in regulation and balancing carbon between the serine cycle and the EMC pathway. A set of transaminases may contribute to carbon partitioning between the pathways. Metabolic pathways for acquisition and/or assimilation of nitrogen and iron are discussed.